KESANTUNAN BERBAHASA DOSEN-MAHASISWA DALAM INTERAKSI PERKULIAHAN DI IAIN TULUNGAGUNG - Mohamad Jazeri; Nany Soengkono Madayani; Susanto Susanto (Jurnal Bahasa Lingua Scientia, 2020)
Politeness plays an important role in interaction in order to ovoid friction and conflict between speaker and hearer. This article aims to describe politeness by lecturer to students in academic interaction at IAIN Tulungagung. This study is qualitatively approached using pracmatics design. The data were collected using technique of observation by listening, writing notes, and participating. The data then, analyzed using interactive model adopted from Miles & Huberman. The data were classified according to face theory of Brawn & Levinson i.e. strategy of positive politeness and strategy of netagive politeness. Data analysis reveals that positive politeness strategies used by lecturer in academic interaction at IAIN Tulungagung are (1) the use of attention to speaker need, (2) the use group identity markers, (3) the use of agreement on the same topics, (4) the use of ovoiding disagreement by pseudo-agreement, (5) expressing understanding of speaker need, (6) the use of being optimistic, (7) involving the hearer in the speaker activities, (8) seeking for reasons or giving question, and (9) extending presents. While negative politeness strtaegies used by lecturer in academic interaction at IAIN Tulungagung are (1) the use of indirect utterances, (2) the use of being pessimistic, (3) minimize burden, (4) the use of respect, (5) asking for apologies, (6) the use of impersonal form, (7) the use of general rules of interaction.